Matrimonial rights of Muslim women in the federal territory / Noraini Wahab - Wahab, Noraini (Faculty of Law, 1986)
The purpose of this paper is to highlight the matrimonial rights of Muslim women. for it is a known fact that not all art' women are aware of their rights. There are some who due to the lack of education. poverty and other factors are still ignorant of thei" full rights under Islam. With the increasing number of divorces in the Federal Territory. women should be more alert to their rights available under Muslim family law,. so that they will not be much oppressed and taken for granted by the men. Thus .. it is of utmost importance that women know the types of relief available during tht' subsistence of marriage and also after divorce. The legislation that governs Muslim women in Malaysia. is peculiar to each state which has its own Administra.tion of' Muslim Law Enuctment.